DO INVESTORS CARE ABOUT TAX AVOIDANCE? EVIDENCE FROM INDONESIA - Verani Carolina; Endah Purnama Sari Eddy (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
The purpose of this study is to investigate the response of investors to instances of corporate tax avoidance in Indonesia, which is typified by corporate risk and firm value. This research employs data from all companies listed on the Indonesian Stock Exchange, with the exception of financial sector companies, for the four-year period between 2020 and 2023. The research method is panel data regression, with the Common Effect Model identified as the optimal regression model. The findings indicate that tax avoidance is associated with an increase in corporate risk, yet in the short term, it is linked to an increase in firm value. This research concludes that investors perceive tax avoidance behavior in a negative light.